Colonial moorings on spatial planning of Mozambique - Santos, Michael M. (2022)
Each country has its spatial planning system, which comprises several instruments and objectives focused on city issues and territorial development. On June 25, 1975, the independence of Mozambique was proclaimed, following the end of the colonial war with the military coup of April 25 in Portugal and the Lusaka agreements on September 7, 1974. Consequently, a new framework establishes the bases of public policies for this country, whose main objective is to fulfill territorial quality concerning the collective culture that integrates the local cultural values. Mozambique was an administrative part of Portugal until 1975. There is still a substantial identity between the two countries, sharing the same language and politics, cultural aspects, and administrative organization. In this sense, the present study aims to present a comparative analysis between Mozambique and Portugal's spatial planning systems, seeking to find common characteristics. In conclusion, this research shows similarities based on spatial land use in Mozambique and Portugal. However, there is a clear contrast between land ownership and access. The level of implementation at a diverse level is notorious. We highlight the example of Beira which has a comprehensive plan based on sustainable development and climate-change-resilient mitigation proposals.